College Teachers' and Administrators' Perceptions Regarding Organization Levels of Schools - KÖPRÜLÜ, Fatma (2020)
The aim of this study is to analyze college teachers 'and administrators' perceptions regarding organization levels of schools. For this purpose, the opinions of 32 teachers who were teaching in the 10grades and 18 administrators at 9 colleges (government and private) in which the college program has been conducted in four cities in TRNC have been taken. After the literature review, specialists' opinions were taken to develop the scale form of the qualitative study. With this scale form opinions of administrators and teachers teaching in classes 10 12 IGCSE, AS and A-Level) were analyzed qualitatively. Data obtained by semi-structured interview form was analyzed using NVivo 12 Plus Program. The Kappa Reliability Coefficient was found as 0.89. As a result of the qualitative study, it was found that school principals have the most important responsibility for the effective organizations at school. Therefore, it can be said that school principals should be able to define the school goals well and balance the relationship between the school stakeholders. It has been concluded that the correct organization has a positive effect on the academic success of the students.